Wet and dry flexural high cycle fatigue behaviour of fully bioresorbable glass fibre composites: in-situ polymerisation versus laminate stacking - Chen, Menghao; Lu, Jiawa; Felfel, Reda M.; Parsons, Andrew J.; Irvine, Derek J.; Rudd, Christopher D.; Ahmed, Ifty (Elsevier, 2017)
Fully bioresorbable phosphate based glass fibre reinforced polycaprolactone (PCL/PGF) composites are potentially excellent candidates to address current issues experienced with use of metal implants for hard tissue repair, such as stress shielding effects. It is therefore essential to investigate these materials under representative loading cases and to understand their fatigue behaviour (wet and dry) in order to predict their lifetime in service and their likely mechanisms of failure. This paper investigated the dry and wet flexural fatigue behaviour of PCL/PGF composites with 35% and 50% fibre volume fraction (Vf). Significantly longer flexural fatigue life (p < 0.0001) and superior fatigue damage resistance were observed for In-situ Polymerised (ISP) composites as compared to the Laminate Stacking (LS) composites in both dry and wet conditions, indicating that the ISP promoted considerably stronger interfacial bonding than the LS. Immersion in fluid (wet) during the flexural fatigue tests resulted in significant reduction (p < 0.0001) in the composites fatigue life, earlier onset of fatigue damage and faster damage propagation. Regardless of testing conditions, increasing fibre content led to shorter fatigue life for the PCL/PGF composites. Meanwhile, immersion in degradation media caused softening of both LS and ISP composites during the fatigue tests, which led to a more ductile failure mode. Among all the composites that were investigated, ISP35 (35% Vf) composites maintained at least 50% of their initial stiffness at the end of fatigue tests in both conditions, which is comparable to the flexural properties of human cortical bones. Consequently, ISP composites with 35% Vf maintained at least 50% of its flexural properties after the fatigue failure, which the mechanical retentions were well matched with the properties of human cortical bones.